Measurement of the average shape of longitudinal profiles of cosmic-ray air showers at the Pierre Auger Observatory - Sciutto, Sergio Juan; Asorey, Hernán Gonzalo; Mollerach, Maria Silvia; Figueira, Juan Manuel; Botti, Ana Martina; Bertou, Xavier Pierre Louis; Supanitsky, Alberto Daniel; Gomez Berisso, Mariano; Lucero, Luis Agustin; Golup, Geraldina Tamara; Melo, Diego Gabriel; Garcia, Beatriz Elena; et al. (IOP Publishing, 2019)
Fil: Sciutto, Sergio Juan. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Instituto de Física La Plata. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Instituto de Física La Plata; Argentina